2014
DOI: 10.1093/hmg/ddu422
|View full text |Cite
|
Sign up to set email alerts
|

Dominant negative effect of polyglutamine expansion perturbs normal function of ataxin-3 in neuronal cells

Abstract: The physiological function of Ataxin-3 (ATXN3), a deubiquitylase (DUB) involved in Machado-Joseph Disease (MJD), remains elusive. In this study, we demonstrate that ATXN3 is required for neuronal differentiation and for normal cell morphology, cytoskeletal organization, proliferation and survival of SH-SY5Y and PC12 cells. This cellular phenotype is associated with increased proteasomal degradation of α5 integrin subunit (ITGA5) and reduced activation of integrin signalling and is rescued by ITGA5 overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 89 publications
3
23
0
Order By: Relevance
“…Indeed, animal models carrying mutant HTT and those lacking HTT normal function show some similarities at pathological and behavioral levels, suggesting a contribution of a reduction in the normal function of HTT to the HD phenotype . In accordance, a study in MJD/SCA3 showed that the lack of ATXN3 produced molecular alterations in a neuronal cell model that overlapped those seen in cells overexpressing expanded ATXN3, and also in neurons from a mouse model of MJD/SCA3, suggesting a contribution of an impaired function of ATXN3 to MJD/SCA3 pathogenesis . In SCA1, in which the toxic gain of function hypothesis is well accepted, additional data suggest that perturbation of a normal ATXN1 function contributes to pathogenesis, namely through changes in specific interactions .…”
Section: Therapeutic Strategies For Polyq Diseasesmentioning
confidence: 77%
“…Indeed, animal models carrying mutant HTT and those lacking HTT normal function show some similarities at pathological and behavioral levels, suggesting a contribution of a reduction in the normal function of HTT to the HD phenotype . In accordance, a study in MJD/SCA3 showed that the lack of ATXN3 produced molecular alterations in a neuronal cell model that overlapped those seen in cells overexpressing expanded ATXN3, and also in neurons from a mouse model of MJD/SCA3, suggesting a contribution of an impaired function of ATXN3 to MJD/SCA3 pathogenesis . In SCA1, in which the toxic gain of function hypothesis is well accepted, additional data suggest that perturbation of a normal ATXN1 function contributes to pathogenesis, namely through changes in specific interactions .…”
Section: Therapeutic Strategies For Polyq Diseasesmentioning
confidence: 77%
“…Increased levels of ubiquitinated substrates have been observed in human SCA3 brain tissue and mouse models of SCA3, possibly reflecting altered mutATXN3 deubiquitinase activity 47 and downstream impairment in proteolytic clearance pathways 48,49 . Using a panubiquitin antibody, we found that poly-ubiquitinated protein levels were slightly but significantly increased by 17% ± 4% in SCA3-hESC relative to WT-hESC (p = 0.015, n = 3 passages per line) ( Figure 3E and 3F), suggesting impairment in ubiquitin-dependent proteasomal clearance.…”
Section: Altered Expression Of Key Protein Clearance Pathway Proteinsmentioning
confidence: 99%
“…As shown in Figure 2A-D, knockdown of ATXN3 significantly altered the processing of the three splicing reporters, suggesting a general deregulation of splicing in the absence of this protein. Interestingly, overexpression of a catalytically inert version of ATXN3 in SH-SY5Y cells (ATXN3_C14A), previously shown to have a dominant-negative effect 25 also yielded similar alterations (Figure 2E). Consistent with a global deregulation of splicing in the absence of ATXN3, microarray analysis (Figure 2F) using specific arrays containing additional probes for exon/exon junctions, confirmed that 1993 genes (43%), from the 7450 differentially expressed probes in ATXN3 shRNA cells, presented differentially regulated alternative splicing events (Table EV1).…”
Section: Resultsmentioning
confidence: 54%
“…With the goal of identifying substrates of the DUB activity in neuronal cells, we searched for changes in the ubiquitome of neuronally differentiated SH-SY5Y cells lacking ATXN3 (ATXN3 shRNA cells – Figure EV1A-B) 25 , taking advantage of a recently developed methodology that combines capture of the whole spectrum of polyubiquitylated proteins in a cell extract using an enrichment by Tandem Binding Ubiquitin Entities (TUBEs) followed by mass spectrometry analysis (TUBEs-LC-MS/MS) 30 . Figure 1A summarizes the steps followed for the purification and identification of the polyubiquitylated proteins in ATXN3 shRNA and scrambled control shRNA (SCR shRNA ) cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation